Evaluation on Bali Mynah (Leucopsar rothschildi Stresemann, 1912) population, result of release process 1998-2015 in Bali Barat National Park, Indonesia - Jarwadi Jarwadi Budi Hernowo; SHINDY HAQUESTA (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Hernowo JB, Haquesta S. 2021. Evaluation on Bali Mynah (Leucopsar rothschildi Stresemann, 1912) population, result of release process 1998-2015 in Bali Barat National Park, Indonesia. Biodiversitas 22: 2699-2710. The release of Bali Mynah (Leucopsar rothschildi Stresemann, 1912) is an attempt to return the bird population to its natural habitat to increase the number of Bali Mynah populations in nature. Bali Mynah population release results that can grow, but slow rate, so that indicates to review technical and management evaluation of Bali Mynah release. The study aims to evaluate the development of the population, the factors that affect population numbers and habitat for the results of releasing Bali Mynah, as well as the security factor. The research was conducted and focused on the Breeding Centre of Bali Mynah (BCBM) in Tegal Bunder, Teluk Brumbun, Teluk Kotal, Tanjung Gelap, and Pos Lampu Merah of Bali Barat National Park (BBNP), Indonesia from May to June 2015. The method of data collection is direct observation, measurement (population with concentration method), interview in relation to management of the bird, and literature. Data analysis was done by calculating the score of the assessment and the animal welfare. The result shows that the Bali Mynah population in Breeding Centre of Bali Mynah in Tegal Bunder has been categorized as good (analyzed from the animal welfare and assessment of the Bali Mynah with a score of 76.53 and 4.32 respectively). Bali Mynah population in the release area is well developed. The BM population has shown survival supported by an abundance of food and water availability, but the movement is still limited (500 m-1000 m) from the release areas.